THE INSTRUCTIONAL DELIVERY OF WRITING COURSE AT ENGLISH DEPARTMENT OF UMS: A NATURALISTIC STUDY - Fibrian Anindyawati; Endang Fauziati (Kajian Linguistik dan Sastra, 2015)
The objective of this research is to get a thorough description of the teaching learning process of Writing Course at English Department of Muhammadiyah University of Surakarta, covering the syllabuses, the learning objectives, the instructional materials, the teachers’ roles, the students’ roles, the classroom techniques, the classroom procedures, the teaching media, and the assessment models. The data of this research were collected through observation, interview, and documentation. This research was a naturalistic study. The result shows that the syllabus used in Writing I II is grammatical syllabus and Writing III IV task-based syllabus. The learning objectives categorized into two namely, general objectives and specific objectives. The instructional materials were divided into three categories: printed materials, visual materials, and materials from the internet. The teachers’ roles were as organizer, consultant, feedback provider, assessor, and motivator. The students’ roles were as active participant, peer reviewer, and peer editor. The classroom techniques consist of brainstorming, discussion, question and answer, self-correction, assignment. The classroom procedures of Writing I II were BKOF-MOT-ICOT; Writing III were reviewing, gathering ideas, organizing, build writing activity; and Writing IV were reviewing, explaining the materials, gathering ideas, organizing, build writing activity. The media used were LCD Projector, board, slides, and videos. The assessment model consisted of: multiple choices, weekly assignments, quizzes, mid-test, and final-test.  Keywords: Instruction, writing course, teaching writing